2019
DOI: 10.1111/jfb.13894
|View full text |Cite
|
Sign up to set email alerts
|

A biflagellate spermatozoon in the African bonytongue Heterotis niloticus (Teleostei, Osteoglossidae)

Abstract: In this transmission electron microscopy study, we describe the ultrastructure of the spermatozoon of Heterotis niloticus (Osteoglossiformes), which is distinguished by having two flagella. Our investigation also highlights the great diversity of sperm cell structures observed across osteoglossiform families, such as aflagellate (Gymnarchidae, Mormyridae), monoflagellate (Notopteridae, Pantodontidae) and biflagellate spermatozoa. As biflagellate spermatozoa are rare in vertebrates, we also summarize the orders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Unfortunately, lack of any studies on spermiogenesis in other osteoglossomorphs precludes the determination of whether they were producing flagellate or aflagellate aquasperm. Until now, the ultrastructure of flagellate spermatozoa is known only for H. niloticus, where biflagellate spermatozoa possess two cytoplasmic canals (Mattei et al ., 2019), and P. afer where Mattei (1970) indicated that a cytoplasmic canal is absent. Spermatozoa lacking a cytoplasmic canal were described in several species of Pimelodidae (Siluriformes): Pimelodus maculatus (Lacepède 1803), Pimelodus ornatus (Kner 1858), Pseudoplatystoma fasciatum L. and Sorubim lima (Bloch & Schneider 1801) (Batlouni et al ., 2006; Quagio Grassiotto & Carvalho, 2000; Quagio‐Grassiotto & Oliveira, 2008), and in the type of spermatogenesis designated as type III in which nuclear rotation does not occur and the flagellum is formed just posterior to the basal body and becomes associated with the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, lack of any studies on spermiogenesis in other osteoglossomorphs precludes the determination of whether they were producing flagellate or aflagellate aquasperm. Until now, the ultrastructure of flagellate spermatozoa is known only for H. niloticus, where biflagellate spermatozoa possess two cytoplasmic canals (Mattei et al ., 2019), and P. afer where Mattei (1970) indicated that a cytoplasmic canal is absent. Spermatozoa lacking a cytoplasmic canal were described in several species of Pimelodidae (Siluriformes): Pimelodus maculatus (Lacepède 1803), Pimelodus ornatus (Kner 1858), Pseudoplatystoma fasciatum L. and Sorubim lima (Bloch & Schneider 1801) (Batlouni et al ., 2006; Quagio Grassiotto & Carvalho, 2000; Quagio‐Grassiotto & Oliveira, 2008), and in the type of spermatogenesis designated as type III in which nuclear rotation does not occur and the flagellum is formed just posterior to the basal body and becomes associated with the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, lack of any studies on spermiogenesis in other osteoglossomorphs precludes the determination of whether they were producing flagellate or aflagellate aquasperm. Until now, the ultrastructure of flagellate spermatozoa is known only for H. niloticus, where biflagellate spermatozoa possess two cytoplasmic canals (Mattei et al, 2019), and P. afer where Mattei (1970) (Mattei et al, 1967(Mattei et al, , 1972. A similar variation in terms of sperm structure (and possibly types of spermiogenesis) has appeared only in Myctophiformes (Neoteleostei, Scopelomorpha), which show both uniflagellate and biflagellate spermatozoa in some species (Hara, 2007;Hara & Okiyama, 1998;Mattei & Mattei, 1976;Ribes et al, 2015) and aflagellate spermatozoa in two species, Lampanyctodes hectoris (Günther 1876) and Diaphus danae (Tåning 1932) (Young et al, 1987).…”
Section: Spermatidsmentioning
confidence: 99%
See 3 more Smart Citations